PENGARUH PENDEKATAN PENEMUAN TERBIMBING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA SEKOLAH DASAR - Zakiyuddin, Zakiyuddin; Margiati, K.Y; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the effect of guided discovery approach to student learning outcome in mathematics class V public elementary school 12 Sepandak D. The Method used in this research is experiment with forms of experimental design quasi research with the study design nonequivalent control grup. Population in this research is all of fifth grade students public elementary school 12 Sepandak D as many as 53 students.The sampling technique in research using probabilitu sampling with a type of simple random sampling. Data collection technique used as test techniques with short stuffing.Result of the data analyze, obtained an average post-test in experimental class obtained at 80,91 while the control class is 73,00. Result of t test obtained tcount (2,137)> ttabel (2,021), its mean Ha accepted. This means that the guided discovery approach has an effect to student learning outcome in mathematics class V public elementary school 12 Sepandak D. Keywords : Guided Discovery Approach, Mathematics